Zwitterionic Nanohydrogels–Decorated Microporous Membrane with Ultrasensitive Salt Responsiveness for Controlled Water Transport. Issue 9 (10th October 2019) - Wang, Aqiang; Fang, Wangxi; Zhang, Jingya; Gao, Shoujian; Zhu, Yuzhang; Jin, Jian
Abstract: Highly sensitive responsiveness is vital for stimuli‐responsive membranes. However, it is a great challenge to fabricate stimuli‐responsive membranes with ultrahigh gating ratio (the ratio of the salt solution permeating flux to the pure water permeating flux) and high response speed simultaneously. In this work, a salt‐responsive membrane with an ultrahigh gating ratio is fabricated via a facile strategy by grafting zwitterionic nanohydrogels onto a poly(acrylic acid)‐grafting‐poly(vinylidene fluoride) (PAA‐g‐PVDF) microporous membrane. Due to the synergistic effect of two functional materials, PAA chains and zwitterionic nanohydrogels tethered on PAA chains, this stimuli‐responsive membrane exhibits an ultrasensitive salt responsiveness with a gating ratio of up to 8.76 times for Na + ions, 89.6 times for Mg 2+ ions, and 89.3 times for Ca 2+ ions. In addition, such zwitterionic nanohydrogels–grafted PAA‐g‐PVDF (ZNG‐g‐PVDF) membranes exhibit very rapid responses to stimuli. The permeating flux changes swiftly while altering the feed solution in a continuous filtration process. The excellent salt‐responsive characteristics endow such a ZNG‐g‐PVDF membrane with great potential for applications like drug delivery, water treatment, and sensors. Abstract : Highly sensitive responsiveness is vital for stimuli‐responsive membranes. In this work, a salt‐responsive membrane is fabricated via a facile strategy by grafting zwitterionic nanohydrogels onto a poly(acrylic acid)‐grafting‐poly(vinylidene fluoride) (PAA‐g‐PVDF) microporous membrane. The stimuli‐responsive membrane exhibits an ultrasensitive salt responsiveness with an ultrahigh gating ratio.